Cumulative Incidence and Risk Factors for Severe Coronavirus Disease 2019 in French People With Cystic Fibrosis. (27th April 2022) - Corvol, Harriet; de Miranda, Sandra; Dehillotte, Clémence; Lemonnier, Lydie; Chiron, Raphael; Danner-Boucher, Isabelle; Hamidfar, Rebecca; Houdouin, Véronique; Macey, Julie; Marguet, Christophe; Murris-Espin, Marlène; Reynaud, Quitterie; et al.
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections are closely monitored in people with cystic fibrosis (pwCF), especially severe cases. Previous studies used hospitalization rates as proxy for severity. Methods: We evaluated data from coronavirus disease 2019 (COVID-19) cases diagnosed in French pwCF over the first pandemic year. Objective criteria were applied for defining severity (eg, respiratory failure and/or death). Data were compared to all French pwCF using the National Registry. Results: As of 30 April 2021, 223 pwCF were diagnosed with COVID-19, with higher risks in adults (odds ratio [OR], 2.52 [95% confidence interval CI, 1.82−3.48]) and transplant recipients (OR, 2.68 [95% CI, 1.98–3.63]). Sixty (26.9%) patients were hospitalized, with increased risk in transplant recipients (OR, 4.74 [95% CI, 2.49–9.02]). In 34 (15%) cases, COVID-19 was considered severe; 28 (46.7%) hospitalizations occurred without objective criteria of severity. Severe cases occurred mostly in adult (85.3%) and posttransplant pwCF (61.8%; OR, 6.02 [95% CI, 2.77–13.06]). In nontransplanted pwCF, risk factors for severity included low lung function (median percentage of predicted forced expiratory volume in 1 second, 54.6% vs 75.1%; OR, 1.04 [95% CI, 1.01–1.08]) and CF-related diabetes (OR, 3.26 [95% CI, 1.02–10.4]). While 204 cases fully recovered, 16 were followed for possible sequelae, and 3 posttransplant females died. Conclusions: Severe COVID-19 occurred infrequently during the first pandemic year in French pwCF. Nontransplanted adults with severe respiratory disease or diabetes and posttransplant individuals were at risk for severe COVID-19. Thus, specific preventive measures should be proposed. Abstract : Severe SARS-CoV-2 infections occur infrequently in people with cystic fibrosis and mainly concern posttransplant adults. Using objective clinical markers, we showed that risk factors for severity include low lung function and diabetes in nontransplanted individuals and posttransplant status.